2013
DOI: 10.1016/j.rmed.2012.12.002
|View full text |Cite
|
Sign up to set email alerts
|

Inhaled corticosteroid use and risks of lung cancer and laryngeal cancer

Abstract: Background: Chronic inflammation has been implicated in the pathogenesis of several cancers, including lung and laryngeal cancer. The objective of the study is to elucidate the association between ICS use and diagnosis of lung and laryngeal cancer. Methods: A nested caseecontrol study based on the Korean national claims database included new adult users of inhaled medications between January 1, 2007, and December 31, 2010. Patients diagnosed with lung cancer or laryngeal cancer after enrollment were identified… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
55
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(56 citation statements)
references
References 43 publications
1
55
0
Order By: Relevance
“…CR markedly increases corticosterone levels and, importantly, adrenalectomy abolishes the inhibitory effect of CR on skin and lung tumors, but not mammary tumors . Recently, it was reported that the use of inhaled corticosteroid is associated with a dose‐dependent reduced risk of lung cancer in humans . CR inhibition of mammary tumors is more associated with decreased IGF‐1 levels than circulating corticosterone .…”
Section: Discussionmentioning
confidence: 99%
“…CR markedly increases corticosterone levels and, importantly, adrenalectomy abolishes the inhibitory effect of CR on skin and lung tumors, but not mammary tumors . Recently, it was reported that the use of inhaled corticosteroid is associated with a dose‐dependent reduced risk of lung cancer in humans . CR inhibition of mammary tumors is more associated with decreased IGF‐1 levels than circulating corticosterone .…”
Section: Discussionmentioning
confidence: 99%
“…had a relatively short follow‐up period, and asthma or other airway diseases without COPD were also included since the study included all subjects using inhaled medications. Smoking status or amount, the most important risk factor for lung cancer, was not evaluated in some previous studies …”
Section: Discussionmentioning
confidence: 99%
“…However, in that case we would expect that there would be an increased risk of lung cancer (or at least no significant and protective effect of ICS use), which was not the case in the observational studies. The influence of protopathic bias was discounted in an observational study evaluating the impact of ICS exposure on lung cancer incidence . This study, which was not included in this review because the study population included subjects with either COPD, asthma or another respiratory condition, reported a significant protective effect of ICS against lung cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Similar to the two observational studies that were included in this review, this protective effect was dose‐dependent. With respect to protopathic bias, those authors performed a sensitivity analysis where exposure to ICS within 3–6 months prior to lung cancer diagnosis was excluded, and the protective effect of ICS persisted . Neither identified observational study used a lagged exposure period to reduce the possibility of protopathic bias in their base‐case analysis; however, Parimon et al .…”
Section: Discussionmentioning
confidence: 99%